Reputation Effects and the Limits of Contracting: A Study of the Indian Software Industry* - Banerjee, Abhijit V.; Duflo, Esther (Quarterly Journal of Economics, 2000)
This paper examines evidence of the role that reputation plays in determining contractual outcomes. We conduct an empirical analysis of the Indian customized software industry, using a data set we collected containing detailed information on 230 projects carried out by 125 software firms. We propose a model ofthe industry where reputation determines contractual outcomes. The evidence supports the view that reputation matters. Ex ante contracts, as well as the outcome after ex post renegotiation, vary with firms' characteristics plausibly associated with reputation. This holds after controlling for project, client, and firm characteristics.